2014
DOI: 10.5455/ijmsph.2014.130920141
|View full text |Cite
|
Sign up to set email alerts
|

Socio-demographic profile of hanging cases at New Civil Hospital, Surat

Abstract: Background: Violent asphyxial deaths are one of the important causes of death nowadays. For reasons not known to others, victims end their life by committing suicide. Hanging is one of the preferred mode of committing suicide, as it supposedly produces painless death as compared to others modes of suicide, and also because it produces instantaneous death. The present study is for looking into demographic profile of the victims of hanging for studying the predisposing factors, and to take preventing measures. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 2 publications
3
2
0
3
Order By: Relevance
“…The above findings are consistent with that done by authors Udhayabanu R et al 9 and Chandegara Paresh Kumar et al 10 . The findings are in contrast to the observations done by author Samanta Ashok Kumar et al 11 at Bhubaneswar where he had found that in 45.7% of cases, hanging is common in illiterate people which is in contrast with our study where we had observed the same percentage to be 11.88%.…”
Section: Discussionsupporting
confidence: 93%
“…The above findings are consistent with that done by authors Udhayabanu R et al 9 and Chandegara Paresh Kumar et al 10 . The findings are in contrast to the observations done by author Samanta Ashok Kumar et al 11 at Bhubaneswar where he had found that in 45.7% of cases, hanging is common in illiterate people which is in contrast with our study where we had observed the same percentage to be 11.88%.…”
Section: Discussionsupporting
confidence: 93%
“…This is very well described in other studies as well. 5 Majority (70%) were found hanging inside their home. This is reported in many other studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Hal ini diperkirakan karena laki-laki memiliki aktivitas yang lebih tinggi dan lebih rentan terhadap stressor. 18 Sebagian besar subjek penelitian berusia ≥50 tahun (85.71%). Hal ini sejalan dengan penelitian oleh Tewksburya, et al (2010) yang menyatakan kejadian bunuh diri paling sering terjadi pada usia >75 tahun (16,9 per 100.000) dan usia 45-54 tahun (16,5 per 100.000).…”
Section: Diskusiunclassified
“…22 Masalah ekonomi banyak berperan dalam memicu bunuh diri pada penelitian ini (30%). Penelitian Chandegara, et al (2014) di India menyimpulkan kasus gantung diri tinggi pada kelompok subjek dengan tingkat ekonomi rendah. 18 Faktor finansial memegang peranan sebesar 7.7% dalam kejadian gantung diri.…”
Section: Diskusiunclassified
See 1 more Smart Citation